Cultivated human intestinal fungus Candida metapsilosis M2006B attenuates colitis by secreting acyclic sesquiterpenoids as FXR agonists. Issue 11 (16th February 2022) - Huo, Xiaokui; Li, Dawei; Wu, Fan; Li, Shenghui; Qiao, Yanling; Wang, Chao; Wang, Yan; Zhou, Changjiang; Sun, Liqun; Luan, Zhilin; Yan, Qiulong; Wang, Jiayue; et al.
Abstract : Objective: Dysbiosis of the intestinal fungal community has been observed in inflammatory bowel disease (IBD); however, its potential role in IBD development and prevention remains unclear. Here, we explored the biological effects and molecular mechanisms of intestinal fungi isolated from human faeces on colitis in mice. Design: Intestinal fungal strains with differential abundance in IBD were cultivated in human faeces and their effects on various mouse models of experimental colitis were evaluated. In addition, the bioactive metabolites secreted by the target fungus were accurately identified and their pharmacological effects and potential molecular targets were investigated in vitro and in vivo. Results: The abundance of Candida spp was significantly higher in patients with IBD. After large-scale human intestinal fungal cultivation and functional analysis, Candida metapsilosis M2006B significantly attenuated various models of experimental colitis in wild-type, antibiotic-treated, germ-free, and IL10 -/- mice by activating farnesoid X receptor (FXR). Among the seven acyclic sesquiterpenoids (F1–F7) identified as major secondary metabolites of M2006B, F4 and F5 attenuated colitis in mice by acting as novel FXR agonists. The therapeutic effects of M2006B and its metabolites on colitis via specific FXR activation were confirmed in Fxr -/- mice. Conclusion: This study revealed that C. metapsilosis M2006B significantly attenuated colitis in mice and identified two acyclic sesquiterpenoids (F4 and F5) as major active metabolites of M2006B. Notably, these metabolites were able to effectively treat experimental colitis by selectively activating FXR. Together, this study demonstrates that M2006B could be a beneficial intestinal fungus for treating and preventing IBD.